2023
DOI: 10.5152/eurjrheum.2022.21090
|View full text |Cite
|
Sign up to set email alerts
|

Oral or Parenteral Methotrexate for the Treatment of Polyarticular Juvenile Idiopathic Arthritis

Abstract: Objective: Subcutaneous methotrexate injections are considered to be more effective or work faster than oral methotrexate. Therefore, the extent and the kinetics of response were analyzed in juvenile idiopathic arthritis patients treated with oral versus subcutaneous methotrexate. Methods: The BIKER databank was searched for biologics-naive juvenile idiopathic arthritis patients treated with methotrexate as initial treatment. The Juvenile Arthritis Disease Activity Scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The current study showed that parenteral MTX is more efficacious in getting a low disease activity (as shown in Table 4, the CDAI score significantly decreased from 13.15±3.25 to 5.57±2.34), whereas oral MTX causes an insignificant reduction in CDAI score from 12.72±3.13 to 8.90±3.08. This result is similar to studies by Bakry et al, and Choonhakarn et al [13,14]. While a study by Heuvelmans et al had some arguments about the efficacy of oral MTX and concluded that tends to be not inferior to the parenteral one, especially when the dose approaches 25 mg weekly [15].…”
Section: Methodssupporting
confidence: 88%
“…The current study showed that parenteral MTX is more efficacious in getting a low disease activity (as shown in Table 4, the CDAI score significantly decreased from 13.15±3.25 to 5.57±2.34), whereas oral MTX causes an insignificant reduction in CDAI score from 12.72±3.13 to 8.90±3.08. This result is similar to studies by Bakry et al, and Choonhakarn et al [13,14]. While a study by Heuvelmans et al had some arguments about the efficacy of oral MTX and concluded that tends to be not inferior to the parenteral one, especially when the dose approaches 25 mg weekly [15].…”
Section: Methodssupporting
confidence: 88%
“…On the other hand, this could reflect a cohort that was relatively tolerable of MTX with less risk of non-adherence issues. MTX intolerance develops mostly within the first year of use and none of the patients in our cohort were tapering MTX or switched the route of administration (as coping mechanism of intolerance) [ 8 , 13 ]. According to our protocols, JIA patient take MTX as long as it is effective as monotherapy in an as high as tolerable dose.…”
Section: Discussionmentioning
confidence: 99%